Design of an economically feasible support for the replacement of pillars in Providencia Mine, Antioquia - Stage 1 (2019)
Pillar replacement in mining works is a technique of using the pillars that are part of the support structures having a high degree of mineralization, which attracts economic interest. The technique consists of replacing the support pillars of the mineral matrix that contain appreciable and beneficial quantities of mineral by artificial pillars that provide geomechanical structure to the operations, generating support and safety benefits greater than or equal to those provided by the original pillars and thus maximizing the intrinsic economic value of the available rock in the operation. Based on the literature regarding design techniques for the assembly of pillars used in underground gold mining, daily and continuous field inspections were conducted for two months, taking the necessary data for the proposed design following ISRM standards for data collection. The proposed pillars must consider a set of operational economic requirements and meet the geomechanical performance required to guarantee the safety and stability of the site. The design consisted of a combination of two types of pillars, one of concrete and one of mesh, cables and sterile material (granodiorite and dyke). The measurements consisted of RMR determination, the dimensions of the current pillars, and the geomechanical condition using detailed scanlines. Subsequently, the information was refined and correlated, and the degree of fracture and safety factor of the original pillars versus those proposed in the new designs were calculated. As a result, the optimal design for the construction of the replacement pillars should have dimensions of 2 x 1.7 x 1.7 meters, achieving a safety factor of 1.36, complying with the geomechanical requirements of safety and stability and yielding a profit of 405 % as a cost-benefit ratio in replacing the original pillars by those proposed in the design; the sterile material and mesh pillars would have dimensions of 2 x 2 x 2 meters.